2017
DOI: 10.1002/prot.25389
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a novel prolidase from Deinococcus radiodurans identifies new subfamily of bacterial prolidases

Abstract: Xaa-Pro peptidases (XPP) are dinuclear peptidases of MEROPS M24B family that hydrolyze Xaa-Pro iminopeptide bond with a trans-proline at the second position of the peptide substrate. XPPs specific towards dipeptides are called prolidases while those that prefer longer oligopeptides are called aminopeptidases P. Though XPPs are strictly conserved in bacterial and archaeal species, the structural and sequence features that distinguish between prolidases and aminopeptidases P are not always clear. Here, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The recombinant ApXPD characterized in this study, however, shows a preference for positively charged Lys-Pro (Tables 1 and 2). Additionally, most prolidases do not hydrolyze Pro-Pro and Gly-Pro except MtXPD [4], XcXPD [4], AnPEPP [16], PlOPAA [39], DrXPP [43], and HsPEPDI [46]. As indicated by the kinetic study, ApXPD may also show allosteric behavior (Table 2).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The recombinant ApXPD characterized in this study, however, shows a preference for positively charged Lys-Pro (Tables 1 and 2). Additionally, most prolidases do not hydrolyze Pro-Pro and Gly-Pro except MtXPD [4], XcXPD [4], AnPEPP [16], PlOPAA [39], DrXPP [43], and HsPEPDI [46]. As indicated by the kinetic study, ApXPD may also show allosteric behavior (Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…In vitro studies have shown that most prolidases ever reported utilize Mn 2+ ion as cofactors (Table S1) [4,28,[37][38][39][40], whereas PfPEPQ, PhPROL, and ScXPD require Co 2+ in their active sites under aerobic assay conditions [25,34,41], as is the case of XPD from A. phoenicis ATCC 14332 (Figure 7). Furthermore, the enzymatic activities of LdPEPQ, LlXPDII, and TsPROL are dependent on Zn 2+ [26,42,43]. In contrast, the activities of AsOPAA, AuOPAA, LcXPD, PfpepQ, PhPROL, and XmXPD were strongly or even completely inactivated by high concentrations of Zn 2+ (Table S1), which is due to the fact that Zn binding decreases the volume of active site pocket for accumulating the substrates [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scarce family of Xaa-Pro peptidases capable of hydrolyzing trans proline-based tertiary amide bonds , includes aminopeptidase P acting on polyamides (also referred to as X-prolyl aminopeptidase) and prolidases acting on dipeptide substrates. ,, Although Xaa-Pro peptidases can display different domain architectures, they share a dinuclear active site embedded in a catalytic domain composed of a curved β-sheet referred to as the “pita bread” fold. The bimetallic catalytic center, typically composed of two manganese atoms in oxidation state +2, displays overall conserved amino acid ligands within this enzyme superfamily. The metals interact with a nucleophilic μ-hydroxide activated by a catalytic glutamate, both of which reside on the same face of the peptide bond. ,, Interestingly, initial visual inspection of available structures of Escherichia coli aminopeptidase P complexed with inhibitors (PDB 1A16 and 1N51 ) revealed a histidine (H243) in spatial arrangement that would fulfill the geometrical criterion for the general acid shown in Figure d.…”
mentioning
confidence: 99%